Agronomic and Physiological Performance of Rice under Integrative Crop Management. (1st January 2016) - Chu, Guang; Wang, Zhiqin; Zhang, Hao; Yang, Jianchang; Zhang, Jianhua
Abstract : Agronomic and physiological performances of a crop are closely associated with the yield and resource use efficiency. This study investigated if an integrative crop management (ICM) in rice ( Oryza sativa L.) could improve agronomic and physiological performances and, consequently, increase grain yield, nitrogen use efficiency (NUE), and water use efficiency (WUE). A japonica hybrid rice cultivar was field‐grown in 2012 and 2013. Three treatments were conducted: no N application, local high‐yielding cultivation method (LHY), and ICM. The ICM consisted of the adoption of three practices: increased plant density, optimized N management, and an irrigation regime of alternate wetting and moderate soil drying. The ICM substantially increased sink size (total number of spikelets per m 2 ), percentage of productive tillers, root oxidation activity, leaf area duration, non‐structural carbohydrate accumulation in the stem, and zeatin (Z) and zeatin riboside (ZR) content in roots and leaves. On average, the ICM increased grain yield by 18 to 19%, agronomic NUE (kg grain yield increase per kg N applied) by 67 to 70%, and WUE (grain yield per unit water consumed) by 27 to 28% over the LHY. The results suggest that the ICM could achieve the dual goals of increasing grain yield and resource use efficiency, and improved agronomic and physiological performances, especially increased sink size and enhanced root and shoot activities during the middle and late growth periods, contributed to high grain yield, NUE, and WUE in rice.